Effect of exogenous melatonin on antioxidant enzyme activities and membrane lipid peroxidation in avocado fruit during ripening - Bich Ngoc, To Thi; Minh Thu, Vo; Phuong Hien, Nguyen Thi; Thanh Tra, Huynh Thi; Duc Anh, Hoang; Thi Hue, Truong (Vietnam Journal of Biotechnology, 2022)
Melatonin functions as a plant growth regulator, has diverse functions and plays an important role in ripening and fruit senescence. In the current study, we investigated the effect of exogenous melatonin (0.1 mM and 0.5 mM) on reactive oxygen species (ROS) metabolism, membrane lipid peroxidation and antioxidant enzyme activity of avocado (Persea americana Mill. cv. 034) during fruit ripening at 22oC ± 1 and 75-80% relative humidity (RH). The results showed that postharvest fruits treated with 0.5 mM melatonin effectively reduced the accumulation of superoxide anion (O2.), hydrogen peroxide (H2O2) and malondialdehyde (MDA) in the mesocarp of the fruit. In addition, melatonin treatment also significantly promoted the activities of superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) in avocado. It is suggested that enhanced antioxidant enzyme activity induced by melatonin treatment may contribute to scavenge ROS and alleviating membrane lipid peroxidation in avocado fruit. The results indicate that the MT application might collectively contribute to the delay senescence and maintain postharvest quality of avocado.